ANALISIS IMPLEMENTASI PROJEK PENGUATAN PROFIL PANCASILA DI SD ADVENT MERAUKE - Karlina Wong Lieung; Dewi Puji Rahayu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to describe the implementation of a project to strengthen the profile of Pancasila students at SD Advent Merauke. This research is descriptive qualitative research. The research subjects were students and teachers at SD Advent. This research was carried out in the odd semester of the 2022/2023 school year. Based on interviews and observations, data was obtained that students were actively involved and very enthusiastic in the Strengthening Pancasila Student Profile project from the beginning to the end of the P5 project activities. Students are very active in participating in P5 project activities on the topic of MANTING. The principal and teacher conveyed the obstacles encountered in the P5 project with the MANTING topic, namely weather-related obstacles. When the rains come, all the land that has been planted with mustard plants becomes flooded and the plants died. During the MANTING project, there was a flood at the end, after the organic mustard greens had been harvested. But in fact, there are still mustard plants left that cannot be harvested because they are submerged in water. The solution taken by the school to overcome this problem is that the school plans to raise the planting area with higher beds so that when the rainy season comes, the plants will still grow well. At the end of the P5 project, all students are involved in harvesting and marketing the produce. mustard greens that have been planted. The students were very enthusiastic about participating in the mustard harvesting activity. The students looked shrewd in tying the harvested mustard greens. This is a new view for teachers and principals regarding students' abilities outside the intracurricular field.